Shifting relationships to place: a relational place-based perspective on SES resilience. Issue 1 (2nd January 2017) - Cretney, R. M.; Bond, S.
ABSTRACT: Disasters literally and figuratively shake the foundations of place in a community. If place is seen as both a construction of and contributor to identity, then the impact of disasters can result in not only physical displacement but can also fundamentally displace community and individual identity. Despite this, resilience theory, a widely used approach for dealing with disaster, provides little empirical or theoretical background on the role of place in shaping response and recovery from disruption. On 22 February 2011, the ground beneath the city of Christchurch, New Zealand, shook, destabilizing the physical and psychological landscape and displacing the foundations of place identity for many communities. Through the case study of Project Lyttelton, a grassroots community organization close to the epicenter of the 22 February earthquake, this paper seeks to understand and explore the nuances of place and identity, and its role in shaping resilience to such displacing events. We argue that place is an integral component of social systems that requires consideration within resilience frameworks in order for social factors to be properly integrated. From this, we make the case for increased awareness of the connections between these processes and the related consequences for post-disaster realities at both the community and policy level.